Medicinal Plant Applications as Traditional and Complementary Medicine by Sabah Ethnicities and the Regulations and Economic View in Malaysia's Healthcare Industry: A Mini Review - Haris, Akid; Nawan, Nico Arnoly; Li Mei, Corinna Au; Abdul Sani, Suraya; Najmuddin, Syed Umar Faruq Syed (Pharmacognosy Reviews)
Plants containing medicinal and therapeutical properties have been utilized by societies around the world as their primary healthcare needs. Numbers of plants with pharmacological/medicinal benefits such as anticancer, antidiabetic, antimicrobial, and antiviral have been evaluated in research studies concerning the crude plant extracts and their phytochemical constituents. However, the traditional knowledge in Sabah, Malaysia is still under-documented despite the fact that it is the home for many different species of flora. Owing to the great biodiversity of different species of the medicinal plants in Sabah, a wide range of phytochemical compounds could be investigated and determined based on the traditional practices of the ethnicities there. The present review paper attempts to discuss the applications of these plants in Sabah in terms of Traditional and Complementary and Alternative Medicine (T&CAM) practices by f ive ethnicities namely, Kadazan/Dusun, Bajau, Murut, Lundayeh, and Rungus along with its advancements in scientific research to understand its effectiveness in treating intended illness or injuries with proper acknowledgement of the involved communities. Additionally, the economic aspects regarding the regulations and recognitions of medicinal plants and T&CAM practices in Malaysia will also be briefly discussed as natural products have now turned into a key issue in industrialized and developing nations.
Keywords: Biodiversity; Sabah; Traditional medicine; Ethnomedicine; Medicinal plants; Economic